2011
DOI: 10.1371/journal.pone.0020098
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable Direct Hemolysin Downregulates Human Colon Carcinoma Cell Proliferation with the Involvement of E-Cadherin, and β-Catenin/Tcf-4 Signaling

Abstract: BackgroundColon cancers are the frequent causes of cancer mortality worldwide. Recently bacterial toxins have received marked attention as promising approaches in the treatment of colon cancer. Thermostable direct hemolysin (TDH) secreted by Vibrio parahaemolyticus causes influx of extracellular calcium with the subsequent rise in intracellular calcium level in intestinal epithelial cells and it is known that calcium has antiproliferative activity against colon cancer.Key ResultsIn the present study it has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…They secrete a wide range of proteins including adhesins, cyclases, metalloproteasephosphatases, hydrolases, hemolysins etc. ( (Chowdhury et al, 2011). This disparity in the role of the hemolysins is a potential factor affecting the mechanism of reduced burden in the bio lm-competent strain-treated PIRC rats and warrants further investigation in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…They secrete a wide range of proteins including adhesins, cyclases, metalloproteasephosphatases, hydrolases, hemolysins etc. ( (Chowdhury et al, 2011). This disparity in the role of the hemolysins is a potential factor affecting the mechanism of reduced burden in the bio lm-competent strain-treated PIRC rats and warrants further investigation in future studies.…”
Section: Discussionmentioning
confidence: 97%
“…The copyright holder for this preprint (which this version posted July 26, 2022. ; https://doi.org/10.1101/2022.07.26.501613 doi: bioRxiv preprint Some reports have suggested that hemolysins promote tumorigenesis (Hernández-Luna et al, 2016), while others propose that bacterial hemolysins could be protective against colon cancer (Chowdhury et al, 2011). This disparity in the role of the hemolysins is a potential factor affecting the mechanism of reduced burden in the biofilm-competent strain-treated PIRC rats and warrants further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…One of the functions of the RTX family of genes is the production of alpha-hemolysin, reported in several Gram-negative bacteria (including E.coli) to be capable of causing urinary tract infections and host tissue damage (Bauer and Welch, 1996;Sasaki et al, 2009;Vigil et al, 2012). Some reports have suggested that hemolysins promote tumorigenesis (Hernández-Luna et al, 2016), while others propose that bacterial hemolysins could be protective against colon cancer (Chowdhury et al, 2011). This disparity in the role of the hemolysins is a potential factor affecting the mechanism of reduced burden in the biofilm-competent strain-treated PIRC rats and warrants further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of cancers have also been associated by an absence or loss of CaSR; pituitary adenomas and colorectal cancer [99-101]. In colorectal cancer a decreased CaSR expression in the colonic epithelium is evident; it is believed at CaSR acts to promote the down-regulation of beta-catenin-mediated transcriptional activation having subsequent effects on cell proliferation [87,102,103]. Functional expression is also identified in the cardiovascular system [91,104,105] and, most recently, in the pulmonary vasculature where it has been implicated in the pathogenesis of PH [106-109].…”
Section: Calcium Sensing Receptor (Casr)mentioning
confidence: 99%